Formulasi Hair tonic Herbal Kombinasi Rosemary, Mint, dan Ekstrak Natural Berbasis Aloe Vera: Pendekatan Fungsional dan Sensorik dalam Pengembangan Produk Kosmetik Alami: Penelitian - Rahmi Mudia Alti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to formulate and evaluate three herbal hair tonic formulas based on aloe vera combined with rosemary, mint, lemongrass, green tea, guava leaf, lemon, and apple cider vinegar extracts. The three formulas (F1, F2, F3) were prepared using commercially available herbal extracts and evaluated for four weeks through observations of color, clarity, aroma, pH, and sediment formation. A sensory test was also conducted with 20 respondents to assess fragrance, comfort, cooling sensation, and overall user preference. The results showed that Formula F3 demonstrated the best stability and received the highest sensory scores due to its balanced aroma, stable pH, and overall comfort. Formula F2 performed well in delivering a strong cooling and refreshing sensation, while Formula F1 showed weaker visual stability. The study concludes that combining herbal extracts can produce a stable and consumer-preferred natural hair tonic, with Formula F3 recommended for further product development.